Optimization of School Facilities in Supporting Academic Achievement and Extracurricular Activities of Students - Mustajib; Nazmul Hoque, Muhammad; Nur Amalia, Zidni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research is motivated by the importance of school facilities as a key supporting factor in improving the quality of the learning process and the holistic development of students' potential. The purpose of this study is to analyze the role of school facilities in supporting the optimization of students' learning achievements and extracurricular activities at SMA Negeri 1 Pare. This research uses a qualitative approach with a case study type, utilizing data collection techniques through in-depth interviews, participatory observation, and documentation study. The research results show that well-equipped and effectively managed school facilities significantly contribute to creating a conducive learning environment, enhancing student motivation, and supporting the success of extracurricular activities. The implications of these findings emphasize that optimal management of educational facilities is a strategic element in improving the quality of education sustainably, both in academic and non-academic aspects.